Research on building sports simulation model warehouse based on the poser software platform - Feng, L.; Peng, Y.; Zang, L. (International Journal of Sports Science and Engineering, 2007)
Building sports simulation model warehouse is very helpful for us to know more about the law of sports movement and it can offer service for teaching, training, scientific research, physical movement design and achievement exhibition. In this paper, it introduces the characteristics of Poser software, the reason why choosing the software being the platform and the exploitation process of sports simulates model.